Term Broad Ligament Pregnancy with a Healthy Newborn (Medicine Today, 2019)
Introduction: Broad ligament pregnancy also known as inter ligamentous pregnancy is a rare type of ectopic pregnancy. It is one type of secondary abdominal pregnancy. Although ultrasonography is usually helpful in making the diagnosis but it is mostly established during laparotomy. Very few successful live births have been reported in this condition, where such pregnancies reached term and with live birth of a baby.Case Report: A case of 30 year old 2nd gravida of 38 weeks gestation with lower abdominal pain for 20 hours was admitted into Sher-E-Bangla Medical College Hospital, Barishal; Bangladesh. She was suggested for caesarean section as the ultrasonogram revealed transverse lie with complete placenta praevia. Intraoperative diagnosis of right sided broad ligament pregnancy was made and an incision was given on the anterior leaf of the broad ligament and a male live fetus was extracted. Post operative period was uneventful. Both mother and baby were discharged on seventh postoperative day in good health condition.Discussion: Broad ligament pregnancy usually results from rupture of tubal pregnancy through the tubal serosa and the mesosalpinx, with secondary implantation of trophoblast between the leaves of broad ligament. Incidence of broad ligament pregnancy is reported as 1 in 300 ectopic pregnancies. The prognosis is poor with the risk of dying from an abdominal pregnancy is 7.7 times higher than from other forms of ectopic pregnancy and often results from a delay in diagnosis. Trans-vaginal rather than transabdominal ultrasonography is superior in the evaluation of ectopic pregnancy. If there is no intrauterine pregnancy on ultrasonography and the ectopic sac is beside the lower part of the uterus a strong suspicion of broad ligament ectopic should be considered. Very rarely such pregnancy may reach up to term. Bleeding from placental implantation site is the most life-threatening complication during laparotomy.Conclusion: Abdominal pregnancy with resultant healthy newborn is very rare. High level of suspicion, careful clinical and ultrasound examinations are the routine means of diagnosis. Bleeding is the single most important life-threatening complication for the mother. Early diagnosis and proper management are vital in order to decrease maternal morbidity.Medicine Today 2019 Vol.31(1): 60-63